2021
DOI: 10.1088/1402-4896/ac0277
|View full text |Cite
|
Sign up to set email alerts
|

Exact calculations of network coherence in weighted ring-trees networks and recursive trees

Abstract: In this paper, we study noisy consensus dynamics in two families of weighted ring-trees networks and recursive trees with a controlled initial state. Based on the topological structures, we obtain exact expressions for the first- and second-order network coherence as a function of the involved parameters and provide the scalings of network coherence regarding network size. We then show that the weights dominate the consensus behaviors and the scalings. Finally, we make a comparison of the network coherence bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Subsequently, additional studies have delved into the analysis of network coherence in deterministic networks. These studies have explored aspects such as introducing weighted factors, scale-free loop structures, multi-layer networks, asymmetric networks, and optimization techniques [10][11][12][13][14][15][16] and many references cited therein. Furthermore, the calculation of network coherence can be achieved through the global mean first passage time of a random walk [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, additional studies have delved into the analysis of network coherence in deterministic networks. These studies have explored aspects such as introducing weighted factors, scale-free loop structures, multi-layer networks, asymmetric networks, and optimization techniques [10][11][12][13][14][15][16] and many references cited therein. Furthermore, the calculation of network coherence can be achieved through the global mean first passage time of a random walk [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of network coherence [1] was introduced to characterize coupled system resistance to noise. In this method, coherence is a measurement of the deviation of each node's state from the average current state and it was proved that it is determined by the Laplacian spectrum [4][5][6] of the underlying network. Therefore, interplays between the network's structural properties and the system robustness to external disturbances [7,8] can be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars take common networks topology as the main research object, and have achieved abundant theoretical results [8][9][10][11][12][13][14][15][16]. Y. Yi et al took Koch Network as the research object to study the first-order coherence of Koch network with leaderless and one leader [8].…”
Section: Introductionmentioning
confidence: 99%
“…X. Wang et al obtained the first-order coherence of 5-rose network and further analyzed the relationships between the first-order coherence and the number of nodes [13]. T. Jing et al studied the first-order coherence of ring-trees networks and recursive trees, and found that the first-order coherence of ring-trees networks are better than that of recursive trees [16].…”
Section: Introductionmentioning
confidence: 99%